2019
DOI: 10.3390/nu11030596
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Chocolate’s Sugar Content Enhances Its Psychoactive Effects and Intake

Abstract: Chocolate elicits unique brain activity compared to other foods, activating similar brain regions and neurobiological substrates with potentially similar psychoactive effects as substances of abuse. We sought to determine the relationship between chocolate with varying combinations of its main constituents (sugar, cocoa, and fat) and its psychoactive effects. Participants consumed 5 g of a commercially available chocolate with increasing amounts of sugar (90% cocoa, 85% cocoa, 70% cocoa, and milk chocolates). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…The findings are consistent with the theoretical and scientific literature indicating that two or more palatability-inducing ingredients at moderate to high levels may be sufficient to induce hyper-palatability (23,27). Our findings expand on the existing literature by highlighting the role of sodium in enhancing palatability, an ingredient that was key in two of our three clusters, as prior research has primarily focused on combinations of fat and sugar (21,22) or fat and carbohydrates (23). In addition, our findings lend further support to the existing literature that has identified fat and sugar as important ingredients that synergistically enhance food palatability (21,22,35).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings are consistent with the theoretical and scientific literature indicating that two or more palatability-inducing ingredients at moderate to high levels may be sufficient to induce hyper-palatability (23,27). Our findings expand on the existing literature by highlighting the role of sodium in enhancing palatability, an ingredient that was key in two of our three clusters, as prior research has primarily focused on combinations of fat and sugar (21,22) or fat and carbohydrates (23). In addition, our findings lend further support to the existing literature that has identified fat and sugar as important ingredients that synergistically enhance food palatability (21,22,35).…”
Section: Discussionsupporting
confidence: 89%
“…For example, several small experimental studies in humans have demonstrated that a combination of fat and sodium (FSOD) may synergistically enhance food palatability and increase consumption by up to 30% (16,17). Others have reported that combinations of fat and simple sugars (FS) may heighten preference and palatability (18)(19)(20)(21) and that consumption of high fat and high sugar may lead to future weight gain (22). Findings from the behavioral literature are supported by the findings of a recent neuroimaging study in humans that reported supra-additive effects of combining fat and carbohydrates; foods with fat-carbohydrate combinations were more efficient in activating brain reward neural circuitry than foods with either fat or carbohydrates alone (23).…”
Section: Introductionmentioning
confidence: 99%
“…We found little evidence that this is the case. In Experiment 3, we tested whether reward uncertainty modulates the experience of rewards in ways that could facilitate consumption (Casperson et al, 2019; Lenoir et al, 2007; van Opstal et al, 2020). We found that reward uncertainty about monetary outcomes makes sweet drinks taste sweeter and elevates hedonic responses among individuals with preferences for high-intensity sweet tastes.…”
Section: Our Experimentsmentioning
confidence: 99%
“…Participants were also allowed to eat as much as they wanted of each of the different chocolates. Casperson et al [3] found that the excitement subscale of the PEQ increased (relative to baseline) after the 90% cocoa. The Morphine-Benzedrine Group subscale (containing questions about wellbeing and euphoria) and the Morphine subscale (focusing on attitudes and physical sensations) increased after the 85th cocoa sample.…”
Section: Increasing Chocolate's Sugar Content Enhances Its Psychoactimentioning
confidence: 99%
“…This study by Caperson and colleagues explored the potential psychoactive effect of chocolate [3]. Participants consumed 5 g of a commercially available chocolate with increasing amounts of sugar (90% cocoa, 85% cocoa, 70% cocoa, and milk chocolate).…”
Section: Increasing Chocolate's Sugar Content Enhances Its Psychoactimentioning
confidence: 99%